Solve: (x + 3)(x - 1) = 32 (there are two answers)

Expert Answers
jeew-m eNotes educator| Certified Educator

`(x + 3)(x - 1) = 32`

`x^2-x+3x-3 -32 = 0`

`x^2+2x-35 = 0`

`x^2+7x-5x-35 = 0`

`x(x+7)-5(x+5) = 0`

`(x+7)(x-5) = 0`

 

So the answers are;

x = -7

x = 5

 

Since we have a quadratic function we only have two solutions

oldnick | Student

`(x+3)(x-1)= 32`

`(x-1+4)(x-1)=32`

`(x-1)^"+4(x-1)= 32`

`(x-1)+4(x-1) +4=36`

`(x-1+2)^2=36`

`(x+1)^2=36`

`x+1=+-6`

`x=-1+-6`          `x_1=-7 `    `x_2=5`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question